0D–2D and 1D–2D Semiconductor Hybrids Composed of All Inorganic Perovskite Nanocrystals and Single‐Layer Graphene with Improved Light Harvesting. (27th December 2017) - Chen, Jia‐Shiang; Doane, Tennyson L.; Li, Mingxing; Zang, Huidong; Maye, Mathew M.; Cotlet, Mircea
Abstract: In this study, inorganic cesium lead iodide (CsPbI3 ) perovskite nanoparticles (PNPs) and perovskite nanowires (PNWs) with single‐layer graphene (SLG) are combined to obtain 0D–2D PNP–SLG and 1D–2D PNW–SLG hybrids with improved light harvesting. Time‐resolved single‐nanostructure photoluminescence studies of PNPs, PNWs, and related hybrids reveal (i) quasi‐two‐state photoluminescence blinking in PNPs, (ii) highly polarized photoluminescence emitted by PNWs and (iii) efficient interfacial electron transfer between perovskite nanostructures and SLG in both PNP–SLG and PNW–SLG hybrids. Doping of poorly absorbing, highly conductive SLG with perovskite nanocrystals and nanowires provides a simple, yet efficient path to obtain hybrids with increased light‐harvesting properties for potential utilization in the next‐generation photodetectors and photovoltaic devices, including polarization sensitive photodetectors. Abstract : Doping of poorly absorbing, highly conductive single‐layer graphene with perovskite nanocrystals and nanowires provides a simple and efficient path to obtain hybrids with increased light‐harvesting properties and improved exciton production for next‐generation photodetectors.